2018
DOI: 10.1002/jum.14885
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‐Enhanced Ultrasound in Extracorporeal Support: In Vitro Studies and Initial Experience and Safety Data in the Extreme Premature Fetal Lamb Maintained by the Extrauterine Environment for Neonatal Development

Abstract: Objectives To evaluate the effects of ultrasound contrast agent (UCA) administration on hemodynamic parameters and support equipment in in vitro and in vivo models of extracorporeal support. Methods In vitro, incrementally increasing bolus doses of a UCA were administered proximal to a membrane oxygenator, and ultrasound cine clips were obtained. The rates of microbubble destruction across the oxygenator and over time were calculated from time‐intensity‐curves. Measurements across the membrane oxygenator were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Ewes were anesthetized with intramuscular ketamine (15 mg/kg) and inhaled isoflurane (1-4 % in O 2 ) and positioned in left lateral decubitus. Ventilator tidal volume (8-10 ml/kg/min) and respiratory rate (10)(11)(12)(13)(14)(15)(16)(17)(18) were adjusted to achieve a maternal end-tidal CO 2 of 35-40mm Hg and arterial CO 2 of 35-45 mm Hg.…”
Section: Anesthesia Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Ewes were anesthetized with intramuscular ketamine (15 mg/kg) and inhaled isoflurane (1-4 % in O 2 ) and positioned in left lateral decubitus. Ventilator tidal volume (8-10 ml/kg/min) and respiratory rate (10)(11)(12)(13)(14)(15)(16)(17)(18) were adjusted to achieve a maternal end-tidal CO 2 of 35-40mm Hg and arterial CO 2 of 35-45 mm Hg.…”
Section: Anesthesia Protocolmentioning
confidence: 99%
“…Lumason® (sulfur hexafluoride lipid-type A microspheres; Bracco Diagnostics Inc., Monroe Township, NJ, USA) ultrasound contrast agent was administered as a bolus via the fetal umbilical vein (ex utero, 0.2mL) or via fetal arterial catheter (in utero, 0.3mL) with simultaneous ultrasound cine acquisition. Previous literature has documented CEUS safety data in the EXTEND model [17]. Ninety-second cine clips were obtained of the brain in a transaxial (ex utero) or coronal (in utero) plane which included the thalami (Figs.…”
Section: Ultrasound Evaluationmentioning
confidence: 99%
“…15 Ewes were anesthetized with intramuscular ketamine (15 mg/kg) and inhaled iso urane (1-4% in O 2 ) and positioned in left lateral decubitus. Ventilator tidal volume (8-10 ml/kg/min) and respiratory rate (10)(11)(12)(13)(14)(15)(16)(17)(18) were adjusted to achieve a maternal end-tidal CO 2 of 35-40 mm Hg and arterial CO 2 of 35-45 mm Hg.…”
Section: Anesthesia Protocolmentioning
confidence: 99%
“…Previous literature has documented CEUS safety data in the EXTEND model. 17 Ninety-second cine clips were obtained of the brain in a transaxial (ex utero) or coronal (in utero) plane which included the thalami ( Fig. 2A).…”
Section: Ultrasound Evaluationmentioning
confidence: 99%
“…[9][10][11] We have previously shown that CEUS can be used safely to evaluate brain perfusion metrics in this model. 12 Using this preclinical ovine model, our objective was to determine the association between fetal hemodynamics and concurrently measured CEUS perfusion parameters to attain greater understanding of the applications of these quantitative techniques.…”
mentioning
confidence: 99%